2023
DOI: 10.3390/foods12061338
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Binary Combinations of Natural Phenolics and Synthetic Food Preservatives against Food Spoilage Yeasts

Abstract: Natural compounds are a suitable alternative to synthetic food preservatives due to their natural origin and health-promoting properties. In the current study, phenolic–phenolic and phenolic–synthetic combinations were tested for their antibiofilm formation, anti-planktonic growth, and anti-adhesion properties against Debaryomyces hansenii, Wickerhamomyces anomalus (formerly Pichia anomala), Schizosaccharomyces pombe, and Saccharomyces cerevisiae. The phenolics were vanillin and cinnamic acid, while the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The results showed that compared with the phenolic-synthetic combinations, the vanillin-cinnamic acid combination had higher activity against spoilage yeast adhesion on abiotic surfaces, biofilm formation, and planktonic growth. Kimani [8] tested the antifungal properties of two phenols and three synthetic preservatives (sodium benzoate, potassium sorbate, and sodium diacetate). The results showed that compared with the phenolic-synthetic combinations, the vanillin-cinnamic acid combination had higher activity against spoilage yeast adhesion on abiotic surfaces, biofilm formation, and planktonic growth.…”
Section: Phenolicsmentioning
confidence: 99%
“…The results showed that compared with the phenolic-synthetic combinations, the vanillin-cinnamic acid combination had higher activity against spoilage yeast adhesion on abiotic surfaces, biofilm formation, and planktonic growth. Kimani [8] tested the antifungal properties of two phenols and three synthetic preservatives (sodium benzoate, potassium sorbate, and sodium diacetate). The results showed that compared with the phenolic-synthetic combinations, the vanillin-cinnamic acid combination had higher activity against spoilage yeast adhesion on abiotic surfaces, biofilm formation, and planktonic growth.…”
Section: Phenolicsmentioning
confidence: 99%
“…Due to their possible impacts on human health, synthetic chemical preservatives, which are widely employed in the food, pharmaceutical, and cosmetic sectors, are causing growing worry. According to studies, some of these preservatives may cause allergic reactions, hormone disturbances, reproductive hazards, skin problems, and a higher risk of developing cancer, among other possible health problems [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%